Robotic-Assisted Microsurgery for an Elective Microsurgical Practice - Gudeloglu, Ahmet; Brahmbhatt, Jamin V.; Parekattil, Sijo J. (Seminars in Plastic Surgery, 2014)
Robotic-assisted microsurgery can be utilized for either intracorporal or extracorporeal surgical procedures. Three-dimensional high-definition magnification, a stable ergonomic platform, elimination of physiologic tremor, and motion scaling make the robotic platform attractive for microsurgeons for complex procedures. Additionally, robotic assistance enables the microsurgeon to take microsurgery to challenging intracorporeal locations in a minimally invasive manner. Recent adjunctive technological developments offer the robotic platform enhanced optical magnification, improved intraoperative imaging, and more precise ablation techniques for microsurgical procedures. The authors present the current state-of-the art tools available in the robotic-assisted microsurgical platform.
Keywords: robotic microsurgery; da Vinci robotic platform; robotic microsurgical instrumentation; optical magnification; intraoperative imaging; micro-Doppler probe; Firefly; Vein Viewer; flexible fiberoptic CO2 laser; water-jet dissection